SEMINAR PENINGKATAN KESADARAN HUKUM PADA REMAJA SISWA SMK NEGERI 2 MAKASSAR - Amrah, Nurmaya; Zainuddin, Kurniati; Nurdin, Muh. Nur Hidayat; Maya, Maya; Kadir, Almanda Meidynita; Mentari, Fardatillah Nur; Alfriani, Alfriani (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
This activity aims to increase legal knowledge and awareness for teenagers through engaging seminars with the theme "Unknowing, then going astray: Obeying the law is cool". The seminar was conducted at SMK Negeri 2 Makassar with a total of 39 participants. The method used is pre-experimental design (non-designs) with the one-group pretest-posttest design technique. Data analysis techniques use descriptive statistical techniques that aim to describe or describe the data that has been collected. Based on the results of the pre-posttest, the results of the study showed an increase and development of positive knowledge and understanding by the participants.